1987
DOI: 10.1097/00000658-198709000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Results with the Mustard Operation in Simple Transposition of the Great Arteries

Abstract: From May 1963 to December 1985, 329 infants and children underwent repair of simple transposition of the great arteries (TGA) using Mustard's technique. To assess improvement, the patients were separated into two groups by date of operation: Group I, May 1963 to December 1973 (N = 106), and Group II, January 1974 to December 1985 (N = 223). The operative mortality was 11 (10.4%) in Group I and two (0.9%) in Group II. The 10-year actuarial survival rate was 73.4% in Group I and 93.7% in Group II. Baffle complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 38 publications
0
20
2
1
Order By: Relevance
“…One patient with Taussig-Bing anomaly developed monomorphic VT late after ASO and received prophylactic ICD. In the present study, no patients developed atrial tachycardia, which is in contrast to the reported high incidence of scar-related atrial tachycardia long-term after the atrial switch procedure [7]. Two patients with simple TGA underwent slow pathway ablation for typical atrioventricular nodal reentrant tachycardia, which has no relationship with the ASO.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…One patient with Taussig-Bing anomaly developed monomorphic VT late after ASO and received prophylactic ICD. In the present study, no patients developed atrial tachycardia, which is in contrast to the reported high incidence of scar-related atrial tachycardia long-term after the atrial switch procedure [7]. Two patients with simple TGA underwent slow pathway ablation for typical atrioventricular nodal reentrant tachycardia, which has no relationship with the ASO.…”
Section: Discussioncontrasting
confidence: 89%
“…It offers an anatomical correction of the anomaly, in contrary to the earlier performed Senning and Mustard procedures. These procedures have well-known complications such as right ventricular failure, tricuspid regurgitation and arrhythmias [6,7]. The results of early-and mid-term follow-up in ASO are good, with low re-intervention rates [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…18 In our series the incidence of late sudden death was 2.9%, which is in agreement with the range of 2-8% reported in the literature. 5,6,[10][11][12][13][14][15][16] …”
Section: Sudden Deathmentioning
confidence: 99%
“…Patients are at increasing risk of late ventricular dysfunction and sudden cardiac death. [2][3][4][5][6][7][8][9][10][11] The exact underlying pathophysiological mechanism is likely to be multifactorial. Myocardial ischaemia in the morphologically right systemic ventricle has been suggested based on the presence of perfusion defects, 9 wall motion abnormalities and features suggestive of fibrosis on late gadolinium cardiovascular magnetic resonance (CMR).…”
Section: Introductionmentioning
confidence: 99%